Analysis of the Modernization of the Tax Administration System in the Context of Optimizing Advertisement Taxes in the District Tax Collection Service Unit. Gambir 2021-2022 - Fatmelia, Henny Rizky (Novatio : Journal of Management Technology and Innovation, 2023)
In the optimization of advertising tax, there still a lack of awareness among the public of taxpayers regarding the advertising tax, and some advertising tax participants either evade or delay their payment obligations. The development of a modernized administration system aims to establish an efficient bureaucracy, particularly to enhance tax revenue. The objective of this research is to examine the modernization of the tax administration system to optimize advertising tax in the tax collection service unit of Gambir Sub-District in 2021-2022. The author applies Diana. Sari’s theory of tax administration modernization, as discussed by Imam Juhadi, and incorporates Person Horoda’s theory of advertising tax optimization. This study adopts a descriptive qualitative research approach. In 2021, the revenue from advertising tax in the tax collection service unit of Gambir Sub-district reached a percentage of 72.71%, while in 2022, it reached 68.89% of its target. It can be noted that in 2022, there was a significant deviation from the predetermined target due to various reasons. Several challenges were encountered by both a officials and taxpayers in fulfilling their obligations.